Research Landscape of Cybersecurity: A Bibliometric and Network Visualization Analysis - Loso Judijanto (Jurnal Multidisiplin West Science, 2026)
The objectives of this research paper are to explore and analyze the research landscape concerning the issues of cybersecurity via application of bibliometric tools and network analysis visualization. Data for analysis was obtained from the Scopus database and analyzed using VOSviewer to evaluate research collaboration patterns, the most prominent papers in the field, and thematic development of research issues in cybernetics. This work will consider the patterns of collaboration among the authors who conducted research in cybersecurity and the citation and co-word occurrences as well. Based on the results obtained, it is possible to say that the field of cybersecurity is very interdisciplinary and geographically diverse. Such countries as the USA and China provide the major part of research in the field. Concerning the thematic patterns identified, it should be noted that although some traditional themes like information security and risk assessments prevail, new trends of integration of cybersecurity with the use of artificial intelligence and Internet of Things become rather popular. Moreover, growing attention is paid to human and organizational aspects related to cybersecurity (decision-making and cybersecurity education).